A cultural fit in cooperation – recognition of the cultural facet of game developers - Klimas, Patrycja (Dopasowanie kulturowe we współpracy międzyorganizacyjnej – profil kulturowy twórców gier w świetle badań empirycznych, 2019)
The relational view perceives cultural fit as a factor allowing cooperation and influencing its performance. It is believed that knowledge about the dominant cultural profile allows organizations to adjust their own cultural profile, and thus increase the cultural fit and improve the cooperation process. The role of cultural fit is of particular importance in markets favoring cooperation and networking, thus our investigation has been sited within the video game industry. Our explorative findings reveal the most typical cultural features, cultural competitive values and models of culture of video game developers. In particular they show, there are differences in cultural aspects between developers of premium and F2P games. In general, organizational cultures of game developers are based mainly on flexibility and best suit the adhocracy culture.
Management Sciences = Nauki o Zarządzaniu, 2019, vol. 24, no. 1; s. 3-10
Keywords: cooperation; organizational culture; cultural fit; cultural similarity; cultural compatibility; współpraca strategiczna; sieci międzyorganizacyjne; kultura organizacyjna; dopasowanie kulturowe; podobieństwo kulturowe